Influence Transformational Leadership and Work Motivation on the Performance of Village Apparatus at the Waekeccee Village Office Subdistrict Lappariaja, Bone Regency - Nasrullah Nasrullah; Andi Jam’an; Moh. Aris Pasigai; Yuzril Yuzril (Universitas Muhammadiyah Makassar, 2024)
This research aims to determine and analyze the influence of transformational leadership and work motivation on the performance of village officials at the Waekeccee Village Office, Lappariaja District, Bone Regency. The type of research used is a quantitative research method with data collection techniques using questionnaires distributed to respondents and the population in the study. This is the Village Apparatus at the Waekeccee Village Office, Lappariaja District, Bone Regency. The analytical method used in this research is multiple linear regression analysis. Then the data obtained is then processed through the application or software Statistical Package For The Social Science (SPSS) version 25. The results of this research show that the variables transformational leadership and work motivation have a positive and significant influence on the performance of the apparatus at the Waekeccee Village office, Lappariaja Bone District, Region